Berberine as a Potential Agent for the Treatment of Colorectal Cancer - Jiang, Xi; Jiang, Zhongxiu; Jiang, Min; Sun, Yan (Frontiers in Medicine, 2022)
Colorectal cancer (CRC) is one of the most commonly diagnosed and deadly malignancies worldwide. The incidence of CRC has been increasing, especially in young people. Although great advances have been made in managing CRC, the prognosis is unfavorable. Numerous studies have shown that berberine (BBR) is a safe and effective agent presenting significant antitumor effects. Nevertheless, the detailed underlying mechanism in treating CRC remains indistinct. In this review, we herein offer beneficial evidence for the utilization of BBR in the management and treatment of CRC, and describe the underlying mechanism(s). The review emphasizes several therapeutic effects of BBR and confirms that BBR could suppress CRC by modulating gene expression, the cell cycle, the inflammatory response, oxidative stress, and several signaling pathways. In addition, BBR also displays antitumor effects in CRC by regulating the gut microbiota and mucosal barrier function. This review emphasizes BBR as a potentially effective and safe drug for CRC therapy.